1989
DOI: 10.1021/bi00452a024
|View full text |Cite
|
Sign up to set email alerts
|

p10 Single-stranded nucleic acid binding protein from murine leukemia virus binds metal ions via the peptide sequence Cys26-X2-Cys29-X4-His34-X4-Cys39

Abstract: The RNA binding protein of 56 residues encoded by the extreme 3' region of the gag gene of Rauscher murine leukemia virus (MuLV) has been chemically synthesized by a solid-phase synthesis approach. Since the peptide contains a Cys26-X2-Cys29-X4-His34-X2-Cys39 sequence that is shared by all retroviral gag polyproteins which has been proposed to be a metal binding region, it was of considerable interest to examine the metal binding properties of the complete p10 protein. As postulated, p10 binds the metal ions C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…This peptide serves as an important model system, as the bound zinc atom is known to exist in a 3Cys-1His tetrahedral environment (South et al, 1989;Summers et al, 1990). Several other peptides and proteins that contain the CCHC motif have been shown by UV-visible and NMR spectroscopic methods to bind zinc via 3Cys and 1 His residues, forming a tetrahedral metal coordination site (Green & Berg, 1989Roberts et al, 1989;Fitzgerald & Coleman, 1991;South et al, 1991). Although nonlinear least-squares fitting of the Fourier-filtered (first coordination sphere) EXAFS data obtained for HIV1-Fl afforded several solutions that are consistent with the EXAFS data alone (Chance, M., pers.…”
Section: Exafs Spectra Of Intact Retroviruses and The Relevance Of CCmentioning
confidence: 99%
See 1 more Smart Citation
“…This peptide serves as an important model system, as the bound zinc atom is known to exist in a 3Cys-1His tetrahedral environment (South et al, 1989;Summers et al, 1990). Several other peptides and proteins that contain the CCHC motif have been shown by UV-visible and NMR spectroscopic methods to bind zinc via 3Cys and 1 His residues, forming a tetrahedral metal coordination site (Green & Berg, 1989Roberts et al, 1989;Fitzgerald & Coleman, 1991;South et al, 1991). Although nonlinear least-squares fitting of the Fourier-filtered (first coordination sphere) EXAFS data obtained for HIV1-Fl afforded several solutions that are consistent with the EXAFS data alone (Chance, M., pers.…”
Section: Exafs Spectra Of Intact Retroviruses and The Relevance Of CCmentioning
confidence: 99%
“…Without exception, retroviral NC proteins (and their gag precursors) contain one or two copies of an invariant CCHC array, Cys-X,-Cys-X,-His-X4-Cys (X = variable or conservatively substituted amino acid) (Henderson et al, 1981), that are essential for RNA genome packaging and infectivity (Gorelick et al, 1988(Gorelick et al, , 1990Meric & Goff, 1989;Aldovini & Young, 1990) and have been proposed to function as zinc-binding domains (Berg, 1986). Although the arrays are capable of binding zinc in vitro (Green & Berg, 1989Roberts et al, 1989;South et al, 1989South et al, , 1990aSouth et al, ,b, 1991Summers et al, 1990;Fitzgerald & Coleman, 1991;Omichinski et al, 1991), the physiological relevance of this CCHC zinc finger motif (previously referred to as a retroviral-type or zinc finger-like motif) has not been firmly established. In fact, it has been reported that avian myeloblastosis virus (AMV) particles lack significant amounts of zinc (Jentoft et al, 1988), which has led to the suggestion that the conserved arrays do not function as zinc binding fingers in mature viruses (Jentoft et al, 1988;Katz & Jentoft, 1989).…”
mentioning
confidence: 99%
“…An examination of the predicted SLU7 protein sequence revealed a region that bears striking similarity to a cysteine-rich zinc knuckle motif of retroviral nucleocapsid proteins {Table 2; Berg 1986;South and Summers 1990). The hallmark of this motif is the consensus sequence CX~CX4HX4C, which coordinates zinc in a manner reminiscent of classical zinc finger proteins (Schiff et al 1988;Roberts et al 1989;Green and Berg 1990;Summers et al 1990;Fitzgerald and Coleman 1991). Note that the relative spacing of cysteine and histidine residues is strictly specified in the case of nucleocapsid proteins, unlike the case of zinc finger proteins.…”
Section: Cloning the Slu7 Genementioning
confidence: 99%
“…Subsequent to assembly and budding, the gag poly (Berg, 1986) that the arrays function by coordinating zinc (Green & Berg, 1989Roberts et al, 1989;South et al, 1989South et al, , 1990a South et al, ,b, 1991Summers et al, 1990Summers et al, , 1992Fitzgerald & Coleman, 1991;Omichinski et al, 1991). In particular, recent zinc-edge extended X-ray absorption fine structure (EXAFS) measurements on intact retroviruses reveal that tightly associated viral zinc, which is present in quantities sufficient to populate the arrays , is coordinated t o the CCHC zinc fingers of the NC proteins in mature virions Summers et al, 1992).…”
Section: Introductionmentioning
confidence: 99%